The Phenomenon of Law and Library Institution - Özer Soysal (Türk Kütüphaneciliği)
The 1961 Constitution is the product ofthe necessity for reorganisation. İn this study, fırstly, the possibilities which emerged on the roads of‘socialisation’ofthe service w ili be defined by folloıving the formalising phases of this lam. İn addition, the tendeııcy that appeared for making autonomies of the library institution ıvill be discussed in this context.